THE PHENOMENON OF MAGIC NUMBERS: THEORETICAL AND METHODOLOGICAL BASIS OF THE INTERSECTION OF MYTH–RITUAL–FOLKLORE (Universal International Scientific Journal, 2026)
This article theoretically explores the phenomenon of “magic numbers” in folklore texts within the framework of mythological thought, ritual practice, and folklore poetics. The attribution of mysterious and sacred meaning to numbers was formed inextricably linked with the ancient human desire to understand the world, the symbolic modeling of natural phenomena, and the rituals regulating social life. Anthropological and cultural-historical research shows that the practice of counting emerged in primitive society not as a logical abstraction, but mixed with collective-mystical imaginations. In this process, some numbers (3, 4, 5, 7, 9, 12, 40, etc.) in addition to being units denoting real quantities, became a cultural code that stably expressed semantics such as “boundary”, “end”, “test”, “blessing”, “protection”, “perfection”. Semiotic and mythosemiotic approaches interpret the number as a structural element of the archaic text, justifying the functioning of numbers as a cosmogonic model and semantic delimiting sign. In structural and poetic functional analysis, numbers are seen as an important link in the plot-compositional mechanism: patterns such as three attempts, three tests, three tasks strengthen the dynamics of fairy tales and epic texts, rhythm and mechanisms of memorization. The article distinguishes the difference between “magic numbers” and “traditional numbers” as a methodological criterion and shows the scientific effectiveness of this distinction in the comparative study of Uzbek and English folklore materials.
Keywords: magic numbers; sacredness; myth–ritual–folklore